Cloning, chromosomal localization, and functional expression of the alpha 1 subunit of the L-type voltage-dependent calcium channel from normal human heart. - Schultz, D (1993)
A unique structural variant of the cardiac L-type voltage-dependent calcium channel alpha 1 subunit cDNA was isolated from libraries derived from normal human heart mRNA. The deduced amino acid sequence shows significant homology to other calcium channel alpha 1 subunits. However, differences from the rabbit heart alpha 1 include a shortened N-terminus, a unique C-terminal insertion, and both forms of an alternatively spliced motif IV S3 region. The shortened N-terminus provides optimal access to consensus sequences thought to facilitate translation. Northern blot analysis revealed a single hybridizing mRNA species of 9.4 kb. The gene for the human heart alpha 1 subunit was localized specifically to the distal region of chromosome 12p13. The cloned alpha 1 subunit was expressed in Xenopus oocytes and single-channel analyses revealed native-like pharmacology and channel properties.